New Jersey Politics and Government : The Suburbs Come of Age - Salmore, Barbara (Book collections on Project MUSE., 2008)
As the United States moves toward becoming a nation of suburbs, New Jersey - its most suburban state - is a place more American should get to know. Its volatile, candidate-centered elections are decided by politically independent suburbanites. New Jersey's experience provides lessons as other states seek to protect the environment, improve the quality of life, and accommodate a multicultural society while sustaining growth and opportunity. Written by two of the most respected political analysts in the state, this is the only book available that provides a comprehensive overview of politics and.